Impact Of The Covid-19 Pandemic On The Indonesian Economy - Lilis Saryani; Abdelina; Ahmad Sayuti Pulungan (CV. Inara, 2021)
This study aims to determine the impact of the COVID-19 pandemic on the Indonesian economy. Until this research was written, 93 countries were found infected with COVID-19. The spread of the COVID19 pandemic eventually brought very bad risks to the world economy, including Indonesia, especially in terms of tourism, trade, and investment. The method used in this research is a descriptive quantitative method using a secondary data analysis approach. Based on the results of the study, the impact of the COVID-19 pandemic caused low investor sentiment towards the market, which in turn led the market to tend to be negative. Strategic steps related to fiscal and monetary are needed to provide economic stimulation. As the COVID-19 pandemic case developed, the market fluctuated more in a negative direction. Not only that, the slow pace of the global economy, especially Indonesian export activities to China also has a significant impact on the Indonesian economy. This is based on a sensitivity analysis that explains that the current slowdown in the global economy has greatly impacted Indonesia's economic growth.